Perfluorinated Alkyl Acids in the Plasma of South African Crocodiles (Crocodylus niloticus) - Christie, Ian (Chemosphere, 2016)
Perfluorinated alkyl acids (PFAAs) are environmental contaminants that have been used in many products for over 50 years. Interest and concern has grown since 2000 on the widespread presence of PFAAs, when it was discovered that PFAAs were present in wildlife samples around the northern hemisphere. Since then, several studies have reported PFAAs in wildlife from many locations, including the remote regions of Antarctica and the Arctic. Although there are a multitude of studies, few have reported PFAA concentrations in reptiles and wildlife in the Southern Hemisphere. This study investigated the presence of PFAAs in the plasma of Nile crocodiles (Crocodylus niloticus) from South Africa. Crocodiles were captured from five sites in and around the Kruger National Park, South Africa, and plasma samples examined for PFAAs. Perfluorooctane sulfonate (PFOS) was the most frequent PFAA detected; with median values of 13.5 ng/g wet mass in crocodiles. In addition to PFOS, long chain perfluorinated carboxylic acids were also detected. Correlations between total length and PFAA load were investigated, as were differences in PFAA accumulation between sexes. No correlations were seen between crocodile size, nor were there sex-related differences. Spatial differences were examined and significant differences were observed in samples collected from the different sites (p < 0.05). Flag Boshielo Dam had the highest PFOS measurements, with a median concentration of 50.3 ng/g wet mass, when compared to the other sites (median concentrations at other sites below 14.0 ng/g wet mass). This suggests a point source of PFOS in this area.